Harmonization of Islamic Law and Customary Law in the Pambissa Kampong Tradition in Latimojong Village - Hamza, Rasida; Kamma, Hamzah; Nawas, Muhammad Zuhri Abu; Cahya, Purnama (Al-Bayyinah, 2024)
The research aims to determine the role and influence of Islamic law in the implementation of the pambissa kampong tradition in Latimojong, the adaptation and change of customary law in the pambissa kampong tradition and its impact on the sustainability of this tradition, and the process of harmonization of Islamic law and customary law in the pambissa kampong tradition and the factors that influence it. The type of research used is empirical legal research. To support this empirical legal research, a normative approach and a sociological approach are used. Shows: (1) The role and influence of Islamic law in the implementation of the Pambissa Kampong Tradition in Latimojong is that customary law adopts Islamic law in its entirety, both in terms of principles and in terms of implementation. Its implementation is adjusted to Islamic law. If there are differences in principle between Islamic law and customary law, then the implementation of Islamic law must be a priority. (2) Changes in customary law in the Pambessa Kampong tradition and its impact on the continuity of this tradition are customary law, which means that rules are made from the behavior of a growing community and developed until it became a law that was obeyed unwritten. So that customary law changes according to the conditions prevailing in society. (3) The process of harmonization of Islamic law and customary law in the Pambessa Kampong tradition and the factors that influence it. Harmonization in question is an effort to harmonize customary law and Islamic law in one national legal system. If all this time there seems to be a difference between customary law and Islamic law, it is urgent to restore harmony between the two.